Recent advances in research of x-c skiing and skijumping - Komi, P.; Seppälä S.; Vähäsöyrinki, P-; Pelkonen J.; Linnamo, V. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Cross-country (x-c) skiing and skijumping are sport events which have been studied quite frequently with kinematic methods. Their merit must be appreciated, because this type of research has considerably advanced understanding of the physical requirements of these two winter sports. Kinetic approaches are more difficult to apply, although needed to understand more clearly the mechanisms involved, The present report gives an overview of the recent developments of the force platform Systems constructed in Vuokatti Sport Institute in Finland for research of x-c skiing and skijumping.